Can biomechanical feedback be used to change the underwater trajectory of a swimming start? - Tor, E.; Pease, D. L.; Maloney, M. A.; Ball, K. A.; Farrow, D. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Adopting an individually optimised underwater trajectory in swimming can reduce resistance and lead to better start performance. This study aimed to determine if quantitative biomechanical feedback could be used to change the underwater trajectory of the swimming start. Three elite freestyle swimmers participated in a six-week test-retest-retention test study. Following the pre-test, a target parameter was assigned to each swimmer to focus upon during the intervention period. Two participants focused on their breakout distance while the third participant focused on the distance of their first kick. Precise biomechanical feedback detailing the distance adjustment required and video from a specialised kinematic analysis system was provided. During the intervention, feedback was faded to facilitate exploration of functional movement solutions. Comparative individual-based analysis using performance curves revealed that participants were able to make rapid changes to their underwater trajectory during the early stages of the intervention. Two participants were able to retain the changes to their technique, although this only transferred to improvements in performance for one swimmer. Precise quantitative augmented feedback can be used to change a swimmer`s underwater trajectory; however, given the complex nature of the swimming start the effects on overall performance require further investigation.